The Effect of Peer Support Group Method Stunting Prevention Education on Mothers' Knowledge and Children's Nutritional Status in Benculuk Village, Cluring District, Banyuwangi - Irfa Lailatul Ni’mah; Siti Maimunah; Atik Badi’ah (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: Stunting is still a problem that often occurs in toddlers,Lack of understanding about nutrition and stunting in mothers can increase the risk of stunting. One of the steps that can be taken to reduce cases of stunting is to spread knowledge about stunting evenly to mothers. Objectives: Determine the effect of providing stunting prevention education to mothers of toddlers using the peer support group method on maternal knowledge and children's nutritional status. Methods: This research is included in Quasi Experimental research with a pretest posttest non-equivalent control group design. The research method used is stunting education using the peer support group method. The research population was mothers who had toddlers aged 7-24 months in Benculuk Village, Cluring District, Banyuwangi Regency. Sampling technique. Purposive sampling technique. The sample size was 60 respondents consisting of 30 people in the experimental group and 30 people in the control group. Univariate data analysis using frequency distribution tables, bivariate analysis using the Wilcoxon test, Mann Whitney test and ordinal regression test. Results: The statistical test results showed a decrease from the intercept only model to the final, namely 27.349 to 10.715 with a difference of 16.630, which means there is a real influence with the presence of the independent variable. If we look at the significance value, there is a significant influence between stunting prevention education using the peer support group method on maternal knowledge and children's nutritional status because the significance value obtained is 0.005 < 0.05. Conclusions: Evaluation after providing education, moreincrease efforts to prevent stunting so that the stunting rate does not increase by consistently providing education about stunting.